Advances of terahertz research and terahertz satellite communications - Shi-Wei Dong; Zhong-bo Zhu; Ying Wang (2011 International Conference on Electronics, Communications and Control, 2011)
Remarkable progress has been made of terahertz technologies such as the source and detector. Great advancement has also been achieved of terahertz systems. Such progress reviewed here presents a big impetus to terahertz satellite communications. For satellite-to-satellite communications terahertz link shows great advantages over either millimeter-wave link or optical link The architecture of terahertz satellite communication systems is proposed.